Learning Outcome Outcomes: An Evaluation of Quality - Sigurgeirsson, Daniel Brur; Larusdottir, Marta; Hamdaga, Mohammad; Daniel, Mats; Jonsson, Bjorn Tor (Proceedings - Frontiers in Education Conference, 2018)
Learning outcomes are a standard specification of knowledge, skills and capabilities that a student is expected to acquire by attending a course or a degree program. While, in theory, the process of evaluating learning outcomes appears to be trivial, in practice it is a complicated and daunting process. In this study, we evaluate how learning outcomes can be effectively applied. The work focuses on the quality of both the specification of the learning outcomes and the assessment of whether these outcomes are reached. We discuss different abstraction levels for learning outcomes and the issue of alignment between high-level and low-level learning outcomes. We also address the criteria for assessing whether a student is meeting a learning outcome. Our work is focused on project-oriented courses, where assessing learning outcomes is seen as particularly challenging. In particular, we draw on an empirical study focused on systematically collecting key performance indicators of the progress towards achieving learning outcomes. The data gathering was done during the course through in-class questionnaires and individual diary notes, as a complementary process to the traditional observations made by the teacher running the course. This data serves as the basis for understanding how individual students advance towards the stated learning goals. We also conducted a focus group discussion after the course to better understand how to interpret the data collected during the course. An important result of our work is forming an understanding and vocabulary regarding learning outcomes and the assessment of how well students meet these learning goals in project-based educational settings. In addition to this, we make the following major contributions: *We present a systematic methodology to gauge how well students meet learning outcomes through in-class self-evaluation.*We present the results of an empirical study of a process-oriented evaluation of the students' development towards stated learning outcomes.*We state some lessons learned from this process that are applicable for designers of project-based courses.